Victimization, perceived organizational support and perceived danger among police officers - Reynolds, Paul (Journal of Theoretical and Philosophical Criminology, 2021)
This study used cross-sectional data from an online survey of police officers in a southern state to examine the potential moderating effect of Perceived Organizational Support (POS) on the relationship between prior victimization and perceived likelihood of victimization (PLOV) using logistic regression. Findings support that prior victimization and POS influence PLOV. However, POS does not moderate the effect of prior victimization on PLOV. This study increases our understanding of how prior victimization and POS is linked to PLOV. Further Policy implications are discussed.